Preparation of uniform starch microcapsules by premix membrane emulsion for controlled release of avermectin. (20th January 2016) - Li, Dan; Liu, Baoxia; Yang, Fei; Wang, Xing; Shen, Hong; Wu, Decheng
Highlights: Starch microcapsules were used as low-cost carriers for the release of pesticides. Starch microcapsules were mass produced and favorable for practical application. The size of microcapsules were uniform and easily adjustable. The release behavior could be tuned by particle size and drug content. Abstract: In recent years, starch microparticles have gained interest in many fields. However, low production, uncontrollable size, and varying size distribution hinder their practical application. Here, we adopt a premix membrane emulsification (PME) method to prepare starch microcapsules at high production rates. The process conditions were optimized to fabricate uniform microcapsules with controllable sizes and narrow size distribution (PDI < 0.1). Through encapsulating avermectin (Av), a kind of water-insoluble pesticide, into the shell of the microcapsules in situ during the process, we developed a pesticide delivery system that enabled a controlled and consistent release of Av over a period of 2 weeks. Kinetic analysis indicated that the mechanisms of Av release involved non-Fickian and Case-II transport. The diameters (0.70–4.8 μm) of the microcapsules and Av contents (16–47%) were adjusted to achieve suitable release profiles. The results will lay the foundation for further field experiments.